1996
DOI: 10.1016/s0006-3495(96)79288-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated DNA adsorption to yeast cells and kinetics of cell transformation by electroporation

Abstract: Detailed kinetic data suggest that the direct transfer of plasmid DNA (YEp 351, 5.6 kbp, supercoiled, Mr approximately 3.5 x 10(6)) by membrane electroporation of yeast cells (Saccharomyces cerevisiae, strain AH 215) is mainly due to electrodiffusive processes. The rate-limiting step for the cell transformation, however, is a bimolecular DNA-binding interaction in the cell interior. Both the adsorption of DNA, directly measured with [32P]dCTP DNA, and the number of transformants are collinearly enhanced with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 28 publications
4
93
1
Order By: Relevance
“…Transient membrane pores are caused by an increase in the dipole moment of hydrophilic phospholipid heads, which move in the same direction as the applied electric field and provoke highly localized dielectric breakages in membrane structure (Kinosita and Tsong, 1977;Neumann et al, 1982;Neumann et al, 1996). Irreversible pores which lead to cellular death are caused by longer pulses and stronger electric fields (Langridge et al, 1987;Shillito et al, 1985), and we found that this occurred with energy inputs of more than 5000 mJ ( Figure 3A) or electric fields stronger than 300 V.cm -1 ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient membrane pores are caused by an increase in the dipole moment of hydrophilic phospholipid heads, which move in the same direction as the applied electric field and provoke highly localized dielectric breakages in membrane structure (Kinosita and Tsong, 1977;Neumann et al, 1982;Neumann et al, 1996). Irreversible pores which lead to cellular death are caused by longer pulses and stronger electric fields (Langridge et al, 1987;Shillito et al, 1985), and we found that this occurred with energy inputs of more than 5000 mJ ( Figure 3A) or electric fields stronger than 300 V.cm -1 ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the data reported by Senaratna et al (1991), we found that non-electroporated protoplasts incubated with plasmid DNA under the same conditions for longer periods of time never showed transient expression of the reporter gene ( Figure 6C). In exponential wave electric circuits, the voltage decays exponentially in the electroporation buffer between the electrodes and the induced energy is dependent on the initially applied voltage and the charge accumulation capacity of the capacitor (Neumann et al, 1982(Neumann et al, , 1996. In this kind of circuit, the time constant (τ) is a function of the electrical resistance (R) and the capacitance (C) of the circuit according to the equation τ = RC, so that for a given capacitor (C = constant) electroporation buffers with reduced ionic force impose less resistance to the movement of charge through the circuit and pulse decay time is longer.…”
Section: Effect Of the Electroporation Buffer On Dna Introductionmentioning
confidence: 99%
“…EDTA, a chelator of Ca 2+ and Mg 2+ (necessary for the enzymatic activity of DNases) decreased electroporation efficiency and resulted in lower cell viability. Neumann et al (1996) suggested that Ca 2+ and Mg 2+ are important for electroporation due to their interaction with the plasmid DNA, decreasing its negative charge and facilitating its interaction with the cell membrane. The results of post-pulse treatment in the present work, similar to those of pre-pulse treatment, suggest however that in electroporation these ions are more important for intra-cellular processes such as the transport of the plasmid through the nuclear pores.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Previous studies have evaluated this approach for in vivo plasmid DNA delivery to muscle. [26][27] In skin delivery, the electroporative-electrophoretic pulse combination significantly increased gene expression levels (Po0.05) when compared to each component pulse (Figure 3).…”
Section: Cutaneous Gene Transfer With Electroporationmentioning
confidence: 99%